Analysis of Sun Protection Factor (SPF) values of Shallot Leaf Extract using UV-Vis Spectroscopy Method - Hajra Hajra; Jumardin Jumardin; Ihsan Ihsan (Media Ilmiah Kesehatan Indonesia, 2026)
A study has been conducted on measuring the sun protection potential of red onion leaf extract with the percentage of pigmentation transmission (%Tp), erythema transmission (%Te), and Sun Protection Factor (SPF) using the UV-Vis Spectrophotometry method. The purpose of this study was to classify the sun protection potential categories of shallot leaf extract. The sunscreen ability test was determined by the calculation method of erythema transmission, pigmentation transmission, and SPF in the wavelength range of 290-320 nm with a distance of 5 nm. From the test, the concentrations of 400 ppm, 600 ppm, 800 ppm, and 1000 ppm were obtained which were included in the Extra Protection category for pigmentation based on the values ​​(%Tp) which were 63.70%, 60.15%, 46.15%, and 47.45%, respectively, all of which were in the Extra Protection category (42 – 86%). The erythema values ​​for each were 63.57%, 59.14%, 45.96%, and 47.31%, respectively. The SPF values ​​were categorized as Minimal Protection with values ​​at concentrations of 400 ppm (1.903), 600 ppm (2.219), 800 ppm (3.284), and 1000 ppm (3.161). The UV protection effectiveness of shallot leaf extract was highly sensitive to pH changes and reached optimum conditions at a pH close to neutral, around 7.07.